TEACHER FACTORS INFLUENCING USE OF QUESTIONING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN MATHEMATICS IN PUBLIC SECONDARY SCHOOLS IN MWALA SUB-COUNTY, MACHAKOS COUNTY, KENYA - MUTHUSI, FRANCIS M. (My University, 2019)
Mathematics teachers play an important function in coaching necessities in arithmetic and in making sure that scholars sign in desirable grades. This is completed with the resource of adopting a couple of additives of wondering strategies. However, in Mwala Sub-county, the scenario is specific with many school students registering low success in arithmetic. Thus, the cause of this look at have become to evaluate trainer elements influencing use of thinking technique on school students’ achievement in arithmetic in public secondary schools in Mwala Sub-county, Machakos County, Kenya. The objectives were: to assess the have an impact on of varieties of mathematics questions, teacher training, experience and thoughts-set in the direction of questioning technique on school students’ fulfillment in arithmetic in public secondary schools. The study changed into guided by using the learning principle. This examine followed blended technique and concurrent triangulation research layout. The look at population became 268 respondents comprising 67 principals and 201 teachers from which a pattern of 160 respondents modified into decided the use of Yamane’s Formula. Stratified sampling has become used to create 8 wonderful strata primarily based totally honestly on the form of zones in Mwala Sub-county. From each place, one essential and 19 mathematics teachers had been determined on the usage of purposive sampling. This way enabled the researcher to pattern eight principals and 152 mathematics teachers. Questionnaires had been used to accumulate quantitative records from arithmetic teachers while interview courses have been used to collect qualitative records from principals. Piloting became finished amongst sixteen respondents from a sample of schools in Mwala Sub-county to check the validity and reliability of studies gadgets. Validity changed into hooked up through judgment thru using specialists in verbal exchange era and school supervisors. Reliability end up hooked up using cut up-half of method. A reliability index of r = 0.847, have turn out to be acquired the usage of Cronbach Alpha Method which indicated immoderate inner reliability. Qualitative information was analyzed thematically based totally on check dreams and provided in narrative shape. Quantitative statistics have been analyzed using descriptive information and inferentially the use of linear regression evaluation in Statistical Package for Social Sciences (SPSS Version 23) and supplied using tables. The observe installed that many mathematics teachers use high-quality easy diploma kinds of questions and disregard complex and application questions which rely on teachers’ schooling, revel in and mind-set which has negatively affected school students’ achievements in mathematics. Thus, the study recommends that mathematics teachers ought to be aware about the forms of questions and how they must area them in the course of high school students. Mathematics teachers ought to go through incompany training in a manner to decorate the questioning approach abilities. Mathematics teachers interact more with professional colleagues by using the use of the usage of attending seminars and workshops designed to enhance their revel in and levels of publicity to particular techniques of wondering. Mathematics teachers must increase the remarkable mindset towards the use of questioning techniques.
Keywords: Mathematics; Teachers